Study of contraceptive use in married women of reproductive age group in urban slum area of western Maharashtra - Mitkari, Kuldeep Kalyanrao; Haralkar, Santosh; Sancheti, Poonam; Gokhale, Ramakant (International Journal Of Community Medicine And Public Health, 2019)
Background: India is world’s second most populous country next to China. Family planning is a key intervention for population control. In urban field, most of population (60%) resides in urban slum area with deprived and vulnerable population. This study was conducted to determine the prevalence of contraceptive use in married women of reproductive age group also to study socio-demographic factors and sources associated with the contraceptive use and the reasons behind not using. Methods: A community based descriptive cross sectional study of 5 months duration was conducted among married women in reproductive age group (15-45 year) resident of urban slum area. 234 samples were selected by simple random sampling method. Data was collected through interviews of study subjects using a semi structured questionnaire. Results: Out of 234 women, 98 (41.9%) women said that they are using some method of contraception, which are condom (6.8%), OC pills (4.3%), copper-T (4.7%) and female sterilization (26.1%). Religion, socio-economic status is not significantly associated with acceptance of contraception, but the education and employment are the key influencers for the contraceptive use. The major sources of information are doctors from the government hospitals and auxiliary nurse midwives. Conclusions: The prevalence of contraceptive use in married women of reproductive age group (15-45 year) in urban slum area is found to be 41.9%. Spacing methods including the modern methods of contraception are not getting accepted. More efforts should be taken to remove fear and misconceptions about contraceptive use.